Optimizing First and Last-Mile Processes for SMEs in Thailand : Implementing a TMS with Lean Concept and SCOR Model for Measurement Efficiency, a Case Study - Tunyaplin, Suratin; Janyapoon, Suwat (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2025)
This research focuses on improving operational efficiency in small transportation companies. The primary objectives are creating a model for SMEs in the transport industry, developing appropriate performance indicators, and implementing a Transportation Management System (TMS) to reduce work redundancies. The study applied the TMS concept based on LEAN and SCOR principles. Results showed that executing TMS reduced working time by 53 minutes for certain activities. However, issuing delivery orders increased from 70 to 120 seconds per bill for 150. Some processes could not be reduced due to legal constraints. The SCOR model helped identify 14 crucial " A Focusing Set of KPIs" suitable for the company's limited resources. The study involved a sample of 12 participants, ranging from operational staff to company owners, using observation and focus group discussions to extract practical indicators for the business. This study demonstrates the feasibility of improving operational efficiency in small transportation companies despite resource and knowledge limitations, using internationally recognized tools and concepts. The results can be applied to other SMEs in the transport industry with similar characteristics and constraints to enhance operational efficiency and competitiveness